Hubungan Karakteristik Individu dengan Kualitas Hidup Pasien Hemodialisis - Yuanita Panma (AKPER Pasar Rebo, 2018)
Hemodialysis is a therapeutic choice that is widely adopted by patients with chronic renal failure. Hemodialysis is carried out for a long period of time and this has a bio, psycho, socio and spiritual impact which can ultimately affect the quality of life of patients.This study aim to find out relationship between individual characteristic and quality of life in hemodialysis patient in Jakarta. Methods: This was a cross sectional study of 148 hemodialysis Indonesian patients, with an average age of 54.86 years and mean length of hemodialysis of 32.67 months. Bivariate analysis using chi-square test and independent t-test. The Kidney Disease Quality of Life-Short Form 36 was used to measure quality of life. Result: The results revealed a significant relationship between quality of life and occupation (p = 0.014) and between quality of life and duration of hemodialysis (p = 0.032). There was no significant relationship between age, education, gender, hemodialysis frequency, marital status, length of hemodialysis with quality of life. Conclusion: There was a significant relationship between occupation and hemodialysis duration with quality of life.